Ana esta furiosa - Nostlinger, Christine; Ballester, Arnal (Madrid : Ediciones SM, 2007)
Ana is angry all of the time and her temper causes her to yell and throw things. Will she ever be able to control her temper?
Translation of: Ana und di Wut.
Keywords: Anger -- Fiction; Temper tantrums -- Fiction; Drum -- Fiction; Emociones -- Novela; Tambor -- Novela; Spanish language materials; Fiction